TiO2 Nanotubes: Nitrogen-Ion Implantation at Low Dose Provides Noble-Metal-Free Photocatalytic H-2-Evolution Activity - Zhou, Xuemei; Häublein, Volker; Liu, Ning; Nguyen, Nhat Truong; Zolnhofer, Eva; Tsuchiya, Hiroaki; Manuela, Killian; Meyer, Karsten; Schmuki, Patrik; Frey, Lothar (Angewandte Chemie International Edition, 2016)
Low-dose nitrogen implantation induces an ion and damage profile in TiO2 nanotubes that leads to co-catalytic activity for photocatalytic H-2-evolution (without the use of any noble metal). Ion implantation with adequate parameters creates this active zone limited to the top part of the tubes. The coupling of this top layer and the underlying non-implanted part of the nanotubes additionally contributes to an efficient carrier separation and thus to a significantly enhanced H-2 generatio
Keywords: H-2 evolution; ion implantation; nitrogen; photocatalysis; TiO2 nanotubes